A Neoteric Double Perovskite Gd2NiMnO6 Nanostructure Electrocatalyst for Augmented Detection of Ecological Pollutant 2, 4, 6 Trichlorophenol. Issue 7 (28th July 2021) - Srinithi, Subburaj; Gopi, Praveen Kumar; Chen, Tse-Wei; Chen, Shen-ming; Kannan, Ramaraj Sayee; Al-Shaalan, Nora Hamad; Ouladsmane, Mohamed; Ali, Mohammad Ajmal; Liu, Xiaoheng
Abstract : 2, 4, 6-trichlorophenol (TCP) is a toxic pollutant harmful to both ecosystems and human health. As such, its detection is important. Here, a novel double perovskite oxide Gd2 NiMnO6 nanostructures (GNMO NSs) fabricated with Screen-printed carbon electrode (SPCE) was used as an electrochemical sensor to analyze TCP in dry red wine. The electrochemical conducting properties of the prepared GNMO NSs were analyzed by Electron impedance spectra. For the first time, the electrochemical sensing performance of a GNMO NSs modified electrode has been scrutinized using cyclic voltammetry and differential pulse voltammetry (DPV) techniques at a potential range from +0.4 to +1.0 V. The detection of TCP at the GNMO modified SPCE electrode explore the high catalytic activity than the bare SPCE. From the DPV results, the linear range and limit of detection for TCP were observed as 0.05–39.05, 47.05–1624, and 0.023 μ M, respectively. The real sample analysis was carried out using red wine to detect the presence of TCP. The GNMO fabricated SPCE sensor displayed a good sensitivity, selectivity, repeatability, and reproducibility.